Optimization of Patrol Activities by the Sabhara Unit in an Effort to Handle Klitih Cases in the Legal Area of the Bantul Police - Dicky Rahman Hakim (Police Studies Review, 2021)
One of the important roles of the National Police is to maintain security and public order in accordance with the provisions of Article 13 of Law Number 2 of 2002. As the times progressed, the problems regarding this role became more complex in various regions. One of them is a case of street crime which is often done by teenagers using sharp weapons or known as klitih. The klitih case caused fear and anxiety in the people of the Special Region of Yogyakarta so that countermeasures had to be implemented. As one of the areas prone to clitih cases, the jurisdiction of the Bantul Police through the Sabhara Unit carries out preventive efforts through active patrols. Based on this background, the researcher analyzed how to optimize patrol activities by the Sabhara Unit in an effort to handle klitih cases in the Bantul Police jurisdiction. In the analysis process, the researcher uses 3 previous studies as references, two of which were carried out in 2017 and one in 2015. The conceptual literature in this study is the patrol concept, sabhara concept, klitih concept, and management theory. The research method used is qualitative with descriptive analysis. Researchers display the results of the application of management theory in problem solving. The focus of the research is on the technical and model of patrols by the Sabhara Unit in handling klitih cases. There are primary and secondary data obtained from interviews, observations, and browsing the literature. Furthermore, data validity is carried out to data analysis. Looking at the geographical conditions, descriptions of human resources, and an overview of the Bantul Police, as well as the Sabhara Unit patrol unit, they still have complete facilities for handling clinical cases. It's just that the obstacles include the use that has not been optimal plus the number of cases that are increasing. The patrol implementation has been based on management theory, namely Planning, Organizing, Acting, and Controlling. Furthermore, an analysis of the influencing factors is carried out consisting of Men, Money, Methods, Materials, Machines, and Market. In order to optimize the clinical case handling patrol, it is carried out using the Mixed Droppoint method. Patrol activities in order to deal with clinical cases in the Bantul Police jurisdiction that are not yet optimal can be carried out by implementing management theory and improving the influencing factors. Furthermore, the Mixed Droppoint method was implemented through the active role of the Sabhara Unit and collaboration with the community and other government agencies.